32.7k views
1 vote
6 times (5-1) = (blank times 5) - (blank times 1)

Somebody please help me i'm confused on how to do this.

User Ascherer
by
4.4k points

2 Answers

4 votes

Answer:

The blank will consist 6.

Explanation:

6*(5-1)=(6*5)-(6-1).

here we have used the law of multipilication to solve it.

User N V
by
5.0k points
5 votes

Answer:

Explanation:

so you you P.E.M.D.A.S to solve for this.

SO paranthesis first 5-1 =4 so 4 times 6 = 24

then take 24 -5 it will = 19

then you do 19 times 1

your answer is 19

User NielsK
by
4.3k points